Immobilization of alcohol dehydrogenase in phospholipid Langmuir-Blodgett films to detect ethanol - Caseli, Luciano (Langmuir : the ACS journal of surfaces and colloids, 2009)
Enzyme immobilization in nanostructured films may be useful for a number of biomimetic systems, particularly if suitable matrixes are identified. Here we show that alcohol dehydrogenase (ADH) has high affinity toward a negatively charged phospholipid, dimyristoylphosphatidic acid (DMPA), which forms a Langmuir monolayer at an air-water interface. Incorporation of ADH into the DMPA monolayer was monitored with surface pressure measurements and polarization-modulation infrared reflection absorption spectroscopy, with the alpha-helices from ADH being mainly oriented parallel to the water surface. ADH remained at the interface even at high surface pressures, thus allowing deposition of Langmuir-Blodgett (LB) films from the DMPA-ADH film. Indeed, interaction with DMPA enhances the transfer of ADH, where the mass transferred onto a solid support increased from 134 ng for ADH on a Gibbs monolayer to 178 ng for an LB film with DMPA. With fluorescence spectroscopy it was possible to confirm that the ADH structure was preserved even after one month of the LB deposition. ADH-containing films deposited onto gold-interdigitated electrodes were employed in a sensor array capable of detecting ethanol at concentrations down to 10 ppb (in volume), using impedance spectroscopy as the method of detection